Exploring Emotional and Cultural Intelligence of Undergraduate International Students at an Indonesian Private University - Silalahi, Ayupitha Tiara; Wulandari, Roosalina; Akbar, Muhamad Fijar Rotul; Kristopo, Hari (AIBPM Publisher, 2022)
By using a phenomenological approach, this study explored the role of emotional and cultural intelligence in the adjustment process of international students. The study engaged 11 participants recruited through purposive sampling. The study employed focused group discussion for the data collection method. The questions were designed to help understand the challenges of adjustment and how emotional and cultural intelligence were exercised to counter those challenges. Findings showed that emotional and cultural intelligence was paramount in enabling international students to be socially integrated. This study aims to offer a greater understanding of the social adjustment challenges of international students while contributing to the existing knowledge and suggesting future research directions.